Prevalence of nonalcoholic fatty liver disease and the related risk factors among healthy adults: A cross-sectional study in Chongqing, China - Kong, Lingxi; Yang, Yang; Li, Haidong; Shan, Youlan; Wang, Xin; Shan, Xuefeng (Frontiers in Public Health, 2023)
Background Epidemiological characteristics of nonalcoholic fatty liver disease (NAFLD) in Chongqing, a west-central city of China, remain unclear. The objective of this study was to investigate the prevalence of NAFLD and the related risk factors among healthy adults for physical examination in Chongqing. Methods A total of 110,626 subjects were enrolled in the present study. Each of the participants underwent physical examination, laboratory measurements, and abdominal ultrasonography. The chi-square test was employed to compare differences in the NAFLD prevalence, and logistic regression analysis was used to estimate the odds ratio for risk factors of NAFLD. Results The prevalence of NAFLD in individuals in the population of Chongqing was 28.5%, and the prevalence in men (38.1%) was significantly higher than that in women (13.6%) (OR = 2.44; 95% CI: 2.31–2.58). NAFLD was more common in men aged 51–60 years and women over 60 years. Approximately 79.1% of the people with obesity and 52.1% of the people with central obesity had NAFLD. The prevalence of NAFLD in people with hypertension and cholelithiasis was 48.9 and 38.4%, respectively. Logistic regression showed that gender, age, body max index (BMI), central obesity, hypertension, impaired fasting glucose/diabetes mellitus (DM), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), hyperuricemia (HUA), alanine transaminase (ALT), and cholelithiasis were independently associated with the presence of NAFLD. Conclusion The prevalence of NAFLD among healthy adults in Chongqing was high. To improve the prevention and management of NAFLD, special attention should be paid to the factors associated with the presence of NAFLD, including higher BMI, higher waist circumference, higher blood glucose, hypertension, hypertriglyceridemia, hyperuricemia, cholelithiasis, and elevated ALT.